AB0023 IMPACT OF METABOLIC CHANGES DURING AGING ON HUMAN EX VIVO NAïVE AND MEMORY CD4+ T CELL FUNCTION. (June 2019) - Chen, Yuling; Löwe, Pelle; Wu, Hao; Buttgereit, Frank; Gaber, Timo
Abstract : Background: Age-related dysfunction in immune cells (immunosenescence), such as T cell dysfunction, may contribute to the development of rheumatoid arthritis (RA). In aged people, senescent T cells tend to produce low amounts of pro-inflammatory cytokines leading to low-grade inflammation. However, cellular metabolism modulates effector functions such as cytokine production and proliferation in T cells by providing energy and building blocks. Metabolically, naïve and memory CD4+ T cells are relatively quiescent immune cells. Currently, the metabolic phenotype of naïve and memory CD4+ T cells and how metabolism affects functions of naïve and memory CD4+ T cells in aged people are not well understood. Objectives: Therefore, we analysed the differences in the metabolic phenotype of peripheral naïve and memory CD4+ T cells in young and aged healthy donors to explore fundamental processes of immune-aging in the pathogenesis of RA. Methods: Naïve and memory CD4+ T cells were isolated from PBMCs of young donors (18-35 years) and old donors (>50 years) by using MACS TM technology. Purity of isolated cell fractions was assessed by flow cytometry. Ex vivo naïve and memory CD4+ T cells were analysed by Seahorse TM Technology to determine proton efflux rate (PER) as a measure of glycolysis (glycPER) and oxygen consumption rate (OCR) as a measure of mitochondrial respiration (mitoOCR). Cytokine expression and secretion was measured by flow cytometry and multiplex assay. Finally, TCR-stimulated memory CD4+ T cell proliferation was determined using CSFE and Ki-67 after 3 days and 4 days by flow cytometry. Results: We included 9 young (20-32 years, 25.0±3.4 years) and 9 aged gender-matched donors (52-67 years, 57.8±5.7 years) for PER and OCR measurement. Memory CD4+ T cells demonstrated higher basal glycolysis, compensatory glycolysis as well as basal OCR and spare respiratory capacity than naïve CD4+ T cells. Memory CD4+ T cells from young donors had higher basal glycolysis, and compensatory glycolysis than aged donors, but lower ratio of basal mitoOCR/glycPER. Although we did not observe differences in intercellular cytokine expression measured by flow cytometry after 5h stimulation of memory CD4+ T cells, we determined a significant higher amount of secreted IL-6, IL-9, IP-10, monocyte chemotactic and activating factor in the supernatant of memory CD4+ T cells from aged donors as compared to those from young donors. Cell division index, proliferation index, percentage of divided cell, and Ki-67 expression after 3 and 4 days of stimulation showed no statistical differences between both groups. Conclusion: Here, we demonstrate a higher basal glycolysis, basal OCR, mitochondrial and glycolytic capacity of human ex vivo memory CD4+ T cells as compared to naïve T cells. A decrease of basal glycolysis, compensatory glycolysis in memory CD4+ T cells of aged people which results in an enhanced cytokine expression can be assumed to culminate in T cell dysfunction leading to the development of RA during aging. Acknowledgement: The work of Yuling Chen was funded by the Chinese Scholarship Council (201606230248). The work of Timo Gaber was funded by the Deutsche Forschungsgemeinschaft (353142848) Disclosure of Interests: Yuling Chen: None declared, Pelle Löwe: None declared, Hao Wu: None declared, Frank Buttgereit: None declared, Timo Gaber Grant/research support from: Pfizer